Employee Motivation at the Secretariat of the Regional People's Representative Council (DPRD) of Ternate City - M.Aksan Botji; Ali Lating; Rasid Pora (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
In a government that prioritizes the principles of good governance, it is necessary to apply a motivation model that is able to inspire employees as much as possible. In this case, the process of internalizing the values of discipline, diligence, thoroughness, enthusiasm needs special emphasis. Leaders should be able to inspire through good examples, such as serious behavior at work, enthusiasm in business, effective behavior, consistent behavior, high work commitment. Motivation carried out by leaders in the Ternate City DPRD Secretariat is carried out with the aim of improving the performance of the organization, productivity and loyalty, discipline, maintaining good relations between leaders and subordinates, forms of work motivation in the Ternate City DPRD Secretariat are carried out through two forms, namely external and internal motivation. The form of external motivation is divided into two, namely the form of positive motivation and negative motivation. Positive forms of motivation are usually given in the form of material and non-material support. Negative motivation in the form of reprimands for employees, reprimands for employees are usually given to employees who do not have the responsibility to complete tasks or applicable rules. The challenge of motivation is how leaders understand the character of each employee, adapt the leadership style to the dynamics and changes that occur, be willing to accept differences and accept criticism, suggestions and different views from subordinates for the progress of the institution.